EFEKTIVITAS PEMBELAJARAN KOOPERATIF TIPE CIRC (COOPERATIVE INTEGRATED READING AND COMPOTITION) PADA KEMAMPUAN PEMECAHAN MASALAH - Khasanah, Binti Anisaul (JURNAL E-DUMATH, 2016)
didikan Matematika, STKIP Muhammadiyah PringsewuEmail: binti_anisa@ymail.comAbstractThe purpose of this study is to know the effectiveness of cooperative learningCIRCS type to trouble-shooting ability on subject rectangular. The subject of thisstudy was all of the students on VII.A class of SMP N Satu Atap 2 Negerikaton inthe academic year of 2014-2015. Method of this study was descriptive analysis.Researcher used observation sheet they were teacherâs ability sheet, activityâsstudent sheet, respondâs student sheet, then to get studentsâ learning achievementwere used essay. Learning indicator that focused on ability aspect, studentactivity and student response is more than 75%, therefore it will increase. Baseon the data, teacherâs ability was 78,23%, studentsâ activity was 76,84%,studentsâ response was 78,48%, base on percentage it will impact learningachievement that reached, based on essay result means that studentâs percentageresult was success and gets above Minimum Completeness Criteria is 77,78%therefore studying result are good, those four indicators learning effectivenessgoal is more than 75%, it means that learning model purpose CIRC tomathematics learning on rectangular material is effective to trouble-shootingability on subject rectangular.Keywords: Cooperative Integrated Reading and Compotition, effectiveness inlearning